Systematic Review and Meta-Analysis of the Prognostic Value of Serum High-Density Lipoprotein Cholesterol Levels for Solid Tumors. - Hao, Bo; Bi, Baochen; Sang, Chen; Yu, Miaomei; Di, Dongmei; Luo, Guanghua; Zhang, Xiaoying (Nutrition & Cancer, 2019)
Numerous studies have demonstrated that serum high-density lipoprotein cholesterol (HDL-C) levels correlate strongly with cancer patient survival. However, other studies have had the opposite results. We therefore conducted a systematic review and meta-analysis to assess the prognostic value of HDL-C levels in people with cancer. We searched PubMed, Embase, and the Cochrane Library (last update by December 28, 2017) for studies evaluating the effect of serum HDL-C levels on cancer patient prognosis. Data from 25 studies covering13,140 patients were included. Combined hazard ratios (HRs) for overall survival (OS) and disease-free survival (DFS) were assessed using fixed-effects and random-effects models. High serum HDL-C levels were associated with better OS (pooled HR = 0.70; 95% confidence interval (CI) (0.60–0.82). In the subgroup, the relative high level of HDL-C yielded a favorable outcome in most of tumor types. However, in the nasopharyngeal carcinoma subgroup, the correlation was not significant (combined HR = 1.31; 95% CI (0.91–1.90)). High serum HDL-C levels were associated with better DFS (pooled HR = 0.64; 95% confidence interval (CI) (0.50–0.81)). This meta-analysis demonstrates that high serum HDL-C levels are associated with better OS in patients with solid tumors, but not nasopharyngeal carcinoma; and high serum HDL-C levels are associated with better DFS.